Qualitative methods as tools for community health assessment - Mershon, Carrie (Kansas State University, 2021)
Children in the U.S. are not getting enough physical activity, which disproportionately affects the 20% of those growing up in rural communities (Troiano et. al., 2008, Brownson et al., 2000; Martin et al., 2005; Fan et al., 2014). Rural population health researchers have attempted to examine communities as social ecological systems impacting the health of all youth living with the community. However, there is lack of effective tools to understand whole-of-community systems and current practices nested within. And the lack of effective tools may contribute to a lack of effective rural population health interventions. Whole-of-community systems and population health researchers and practitioners need tools that can assess local social structure and processes in rapid manner at minimal costs and by people living within the communities who have limited training. Therefore, the purpose of this dissertation is to examine the utility of drawing on qualitative methods as tools for locally driving community population health assessment and intervention planning. Chapter two provides a review of current health promotion research terminology. Health promotion terms identified included membership components such as multisector, multiorganization, and constituency; and community group identification terms such as partnership, collaborative, and coalition. While these words are different, they are all used to describe the same concept, a community group as a vehicle to impacting population health. Findings demonstrated that community population health research falls victim to the jangle fallacy, where different vocabulary is use for the same construct or the same vocabulary is used for different constructs. The danger in the jangle fallacy is it prevents researchers from effectively communicating findings. Chapter two is a scoping review with searches in PubMed, PsycINFO, and Google Scholar databases for articles published 2002 through December 2018 using search terms: health, multisector, collaboration, organization, and sector. The search included grey papers from conferences and group collaborations, online tools, and book chapters to ensure thorough representation. Chapter two fills a gap in the population health literature as a review and analysis of the terms. Chapters three and four focus on the utility of two qualitative assessment tools for community health assessment and planning of whole-of-community health improvement interventions targeting youth population PA improvement. Rural youth assessment methods and investigations are described using data collected in a community (Midwest, KS) in Fall 2018-Spring 2019. The two phases complemented each other for this dissertation but could be implemented independently from one another. Chapter three focuses on the first phase, identifying youth physical activity settings using photovoice. Photovoice empowers participants to engage in documentary photography to share their experiences regarding specific topics. Photovoice is effective with many diverse populations, including lower-income/minority adults and youth, and promotes participant ownership of the research (Kramer et al., 2013; Yi-Frazier et al., 2015). Chapter three models the feasibility of photovoice to document the physical activity behavior settings as part of the local community action process and identifies rural behavior settings for physical activity from the perspective of fourth through sixth graders in November 2018 in Midwest, Kansas. The photovoice process described includes identifying the setting, a novel learning activity, focus groups, analysis, and culturally contextualizing the findings. The physical activity behavior settings identified by fourth- sixth graders included: organized youth sport, 4-H and scouting organizations, church, school, and home. Chapter four focuses on a mini ethnographic case study of one of the locations identified by youth using photovoice, the local 4H club. Mini-ethnographic case study methods were used to assess the current routines and organizational structure. Mini-ethnographic case studies provide a way to study culture while benefitting from the reasonable timeframe and minimal costs of a case study. Chapter four describes community leader-friendly protocols for writing a mini-ethnographic case study report and features a report for the Midwest 4H Club. The protocols of using mini-ethnographic case study methods to examine routine and organizational structure include: selecting a setting, making contacts, observations, interviews, reviewing additional sources, transcription, analysis, and writing a report. A mini-ethnographic case study report was produced and discussed as a tool for communities to complete their own assessments. In conclusion, this dissertation examines the utility of qualitative methods as tools to improve communities’ ability to investigate and plan for interventions targeting positive changes to whole-of-community population health. This dissertation focused on youth population health physical activity improvement and community assessment tools to efficiently and effectively collect community asset-based investigation information for health promotion intervention planning. Future steps include examining the use of these tools on whole-of-community population health intervention implementation and effectiveness
Keywords: Collaboration; Community health improvement; Photovoice; Mini-ethnographic case study; Community health assessment; Community health needs assessment